Local Knowledge of The Community in Mekarwangi Village on Long-Tailed Macaque (Macaca fascicularis) - Rehansha, Canaya Vania; Hasan, Rusdi (Universitas Muhammadiyah Surakarta, 2024)
Local knowlede is a phenomenon that is felt and experienced by the people of a particular area who have local understanding regarding the natural resources found in the surrounding environment. One of this knowledge is about long-tailed macaque (Macaca fascicularis). This research aims to examine local knowledge of the community regarding long-tailed macaque in Mekarwangi Village which borders Taman Hutan Raya Ir. H. Djuanda which is one of the long-tailed macaque conservation sites. The method used in this research is a qualitative approach through observation, semi-structured interviews, and strengthened by literature study. The result obtained were analyzed descriptively. The reseach result show that the community knows about the existence of long-tailed macaque. Community interactions with long-tailed macaque pose a threat to long-tailed macaque, some individu of long-tailed macaque be arrasted because people are disturbed by their existance. The majority of community in Mekarwangi Viilage know the food, habitat, and daily activities of long-tailed macaque from daily observation and some knowledge passed down from previous generations.